Discrimination in an Equilibrium Search Model - Black, Dan A. (Journal of Labor Economics, 1995)
I construct an equilibrium search model where some employers have a distaste for hiring minority workers and show that this bias results in economic discrimination against minority workers. Although only unprejudiced firms hire minority workers, minority workers receive lower wages than workers not facing discrimination whenever any employers in the market have a distaste for minority workers. One implication of the model is that gender or racial wage differentials understate the utility loss from discrimination. In addition, the wages of minority workers increase when their proportion increases in the labor market.